Prenatal diagnosis of ductus venosus agenesis: a retrospective study of associated cytogenetic/congenital anomalies - M. Özsürmeli; M. Sucu; E. Arslan (IMR Press, 2020)
Introduction: Absence of the ductus venosus (ADV) is a rare vascular anomaly often associated with fetal cardiac/extracardiac anomalies, aneuploidies, and hydrops. This study assesses the abnormal venous circulation, associated malformations, and chromosomal anomalies of ADV. Materials and Methods: The authors performed a retrospective study of 14 cases with ADV diagnosed by the prenatal ultrasound in tertiary referral center from 2009 to 2017. Results: The authors detected 14 patients of ADV. Karyotyping was offered to all cases, and four patients accepted the procedure. Normal karyotype was found in three out of four cases, while one case had 45, X0. Five cases underwent termination of pregnancy, six cases died at neonatal period due to accompanying cardiac anomalies, and heart failure. Three cases survived (the oldest baby is 4-years-old now). Umbilical vein (UV) was connected to portal venous system (PVS) in two cases (intrahepatic drainage, one of them is surviving), while UV was connected to systemic venous circulation in 12 cases (extrahepatic drainage, two of them are surviving). In five cases there was no other reason that might explain cardiomegaly and hydrops except ADV (two of them is surviving). Three cases were diagnosed as cystic hygroma in first trimester additionally found ADV. All of surviving fetuses delivered after 35th weeks of gestation. Conclusion: The presence fetal hydrops, accompanying congenital anomalies, and prematurity are associated with poor prognosis in fetuses with ADV. In isolated cases, the prognosis is generally good.